Pelatihan Penerapan Konsep Keuangan bagi Kepengurusan Koperasi Mahasiswa (KOPMA) Universitas Lampung - Manan, Mohammad Athian; Mufahamah, Euis; Nursari, Ayu; Sejati, Hiro (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This community service program was conducted at the Student Cooperative of Lampung University (Kopma Unila) with the aim of enhancing the financial literacy of its board members. The program involved 60 Kopma Unila board members and included education on financial management, the culture of saving, and investment. The methods used consisted of material presentations, interactive discussions, and hands-on practice. The results of this activity showed a significant increase in the understanding and skills of the board members regarding personal and organizational financial management. This financial literacy education is expected to help Kopma Unila board members manage the cooperative's finances more effectively and efficiently, as well as avoid impulsive behaviors and a consumerist culture. The program also provides recommendations for advanced training and the integration of financial literacy into cooperative activities. These findings underscore the importance of financial literacy in the healthy and sustainable management of cooperatives.